Learning commons : evolution and collaborative essentials - Schader, Barbara; ScienceDirect eBooks (Oxford, England : Chandos Publishing, 2008)
This book examines successfully planned and implemented learning commons at several different academic institutions around the world. These case studies provide a methodology for effective planning, implementation and assessment. Practical information is provided on how to collaborate with campus stakeholders, estimate budgeting and staffing and determine the equipment, hardware and software needs. Also provided are memoranda of understandings (MOUs), planning checklists and assessment tools. This book reflects a unifying focus on both the evolution of learning commons to learning spaces and the collaborative aspect of co-creating learning spaces. Unique case studies representing very different types of Information Commons, Learning Commons, Faculty Commons and other Learning SpacesInternational breadth and depth is assured through inclusion of case studies from Canadian, New Zealand, Australian and European institutions in addition to six in the United StatesPractical checklists of planning and implantation considerations, as well as memorandum of understanding (MOU) templates, form the appendices.
1. From Information Commons to Learning Commons and learing spaces: an evolutionary context / Mary M. Somerville and Sallie Harlan -- 2. Circle of service: a collaborative Information Commons planning model / Barbara I. Dewey -- 3. The Information Commons at the University of Calgary: building on collaboration -- a case study / Susan Beatty -- 4. Building for learning: synergy of space, technology and collaboration / Susan Thompson and Gabriela Sonntag --5. The Saltire Centre and the Learning Commons concept / Jan Howden -- 6. Transforming library space for student learning: the Learning Commons at Ohio University's Aiden Library / Gary A. Hunt -- 7. Supporting the Learning Commons concept in 'real life' / Jennifer Stringer -- 8. Putting learners at the centre: the Learning Commons journey at Victoria University / Shay Keating, Philip G. Kent and Belinda McLennan -- 9. Improving student life, learning and support through collaboration, integration and innovation / Crit Stuart -- 10. The Information Commons at the University of Auckland: improving student life, learning and support through co-location, collaboration, integration and innovation / Hester Mountfield -- 11. Beyond Facebook: thinking of the Learning Commons as a social network / Jill McKinstry.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed February 6, 2014).
Elsevier
Keywords: Information commons; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Information commons; Librarianship & information science (Australia, New Zealand); Electronic books